REVIEW OF CORPORATE SOCIAL RESPONSIBILITY ON CORPORATE FINANCIAL PERFORMANCE IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Reza Ersan; Haninun Haninun; Khairudin Khairudin (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Corporate Social Responsibility (CSR) has emerged as an essential element of corporate operations, signifying a company's dedication to tackling environmental, social, and ethical concerns. This study aims to analyze the impact of corporate social responsibility (CSR) on the financial performance of Food and Beverage companies listed on the Indonesia Stock Exchange from 2016 to 2022. The Global Reporting Initiative (GRI) index is used as a measurement tool for CSR. The independent variable in this study is CSR, while the dependent variable is either Return on Assets (ROA) or Return on Equity (ROE). The research focuses on companies in the food and beverage subsector listed on the IDX during the specified period. The sample for this study is selected using the purposive method, which involves predetermined standards. Secondary data from the Indonesia Stock Exchange (IDX) for the period 2016 to 2022 is utilized for analysis. The findings of this study indicate that CSR has an insignificant positive impact on ROA, but it does have a significant positive impact on ROE.